THE EFFECT OF USING QUESTION AND ANSWER RELATIONSHIP (QAR) STRATEGY ON READING COMPREHENSION - Siagian, Abdul Rahman (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Problem in this research is how to improve reading comprehensionby using Question and Answer Relationship (QAR) strategy at the X Grade of SMA Negeri 1 AngkolaTimurKabupatenTapanuli Selatan. Thus, the objective of this research is to know if there is any significant effect of using Question and Answer Relationship (QAR) strategy to studentsâ€™ reading comprehension. The Quantitative Method by using experimentaltype research to conduct this research. Population Â of this research was the grade X students consist of 151 students while for tecnique of taking the sampling by using cluster sampling that is 36. The instrument of this research is test about reading comprehension. Based on the data that has been analyzed, it can be found that (1) the studentsâ€™ achievement in reading comprehension byÂ  using Question and Answer Relationship (QAR) strategy) at the categorized is â€œenoughâ€ (69.72), (2) their value beforeÂ  using Question and Answer Relationship (QAR) strategy it can be categorized â€œenoughâ€ (61.94), and (3) there was a significant effect of using Question and Answer Relationship (QAR) strategy on reading comprehension. It meant that the hypothesis was accepted.